The weight of a tooth - Perros, Robyn Helen (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2020)
My thesis is a fragmented, non-linear novella, comprised predominantly of experimental prose- poetry and fiction short-stories. I have chosen this approach in form to further explore my interest in ancestry and trauma, death and image-making, "reality" and fantasy, and the tension these invisible barriers create between the inner and outer worlds in which we simultaneously navigate, remember and forget. This thesis has been influenced both in form and content by the works of Eduardo Galeano, Osama Alomar, Lidia Yuknavitch, Susan Steinberg, Claudia Rankine, Lance Olsen, and Yasunari Kawabata, among others.
Keywords: South African fiction (English) -- 21st century